Cattle Metapodium Bone Fragments of Early Neolitic and Eneolitic Period from Archaeological Site Vučedol (Vukovar, Croatia) - Hincak, Zdravka (Array, 1997)
We researched osteological remains of cattle metapodium which have been digged at the Vučedol site during 1984 and 1985. All remains of originate from early Neolithic (Starčevo culture) and Neolithic (Baden, Kostolac and Vučedol culture) period. During the research osteometrical and morphological treatments were used. Metatarsal and metacarpal boone fragments of cattle point at percentual changes in cattle aboundance as domesticated and feral, hunting animal during different cultural period from early neolithic to late eneolithic period. At some time distinctive osteological remains of cattle divided cattle in two species, feral and domesticated one and one subspecies or mixed form with characteristic of both species